4 Leading education in a pandemic – the 'LEAP' project. (16th November 2020) - Tiwari, Neil; Troth, Laura; Husain, Syed; Wood, James; Hayes, Patrick; Carpenter, Lynn
Abstract : Covid 19 drove unprecedented changes in healthcare provision, necessitating a paradigm change by the healthcare workforce incorporating new clinical knowledge and rapid upskilling in competence. The LEAP Project established a novel system for dissemination of vital role-appropriate training. Project analysis was disseminated to relevant stakeholders via departmental clinical leaders, facilitated by a Directorate Operations Centre (DOC) established at onset. This ensured integration of training within clinical care delivery. The target audience comprised multidisciplinary critical care and anaesthetic staff, and was then expanded to include the wider workforce. Phase one involved drafting a statement of requirement and needs analysis, determined by relevant clinical and educational stakeholders as informed by recommendations from Public Health England, the Royal Colleges and Health Education England. This informed a framework of dynamic role and domain specific training. Leadership was delegated to multidisciplinary educational leads, ensuring academic rigour and credibility. Reciprocal escalation ensured consideration of workforce planning, future-proofing and sensitivity to individual concerns. Subsequent training incorporated a multimodal educational approach. Participant feedback and formal peer review enabled reflection on earlier training delivery, enabling dynamic adaptation of training objectives to ensure relevance and consistency. Almost all 271 nurse upskilling candidates reported a significantly increased knowledge base post session. For Covid 19 teaching days, 90% of 191 candidates reported sessions were at an appropriate level of teaching. All 55 multidisciplinary simulation candidates reported 100% satisfaction. This project dynamically considered all facets of workforce planning and care delivery. We have proven that rapid institution of a functional, multifaceted education programme in response to a crisis is both feasible and practical.